Stjepan Radiþc, the Croat Peasant Party, and the politics of mass mobilization, 1904-1928 - Biondich, Mark (University of Toronto Press, 2000)
The name Stjepan Radic is as well known to Croatians as Sir John A. MacDonald is to Canadians. In 1904, Radic mobilized the peasantry to form a populist movement that resulted in the Croat Peasant Party. The CPP fought to reform Yugoslavia's centralist state system and to amend the structural flaws of the parliamentary system. His assassination in 1928 marked the end of the country's short democratic experience; a royalist dictatorship immediately followed. Croatia failed to achieve statehood or autonomy within Yugoslavia, but Radic's indisputably dominant role in the formation of Croatian national consciousness is widely celebrated among Croatians today. The story of this charismatic, ideologically eclectic politician and his role in nation-building makes for fascinating reading. In North America, with our increasing involvement in the political conflicts of the former Yugoslavia, we cannot afford to remain ignorant of the major historical forces involved in the early Serb/Croat struggles for power and identity. This is an essential work for political scientists and other specialists in the area.